2015
DOI: 10.1177/1474515115602677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of telehealth service for patients with congestive heart failure in the north of Israel

Abstract: During the year of use in telehealth service for congestive heart failure parameters of hospitalization were improved, together with parameters of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
(38 reference statements)
0
13
0
5
Order By: Relevance
“…In terms of cost effectiveness, the results of the present study are similar to other studies that also demonstrated economic benefits from similar interventions[ 28 30 ]. As in previous studies[ 28 , 31 , 32 ] the study population consisted of CHF patients 65 years of age and above with NYHA Class 3–4 severity and repeat, prolonged hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cost effectiveness, the results of the present study are similar to other studies that also demonstrated economic benefits from similar interventions[ 28 30 ]. As in previous studies[ 28 , 31 , 32 ] the study population consisted of CHF patients 65 years of age and above with NYHA Class 3–4 severity and repeat, prolonged hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were selected from three health care centres by handing out the questionnaires that measure the quality of life based on baseline physical measurements and demographic characters. Another service-evaluation retrospective study that lasts for 12 months, conducted by Eilat-Tsanani et al (2016) in Israel, investigated the change in the quality of life and re-hospitalisation rate of patients. Veenstra et al (2015) conducted an optimized care program with 102 patients in the Netherlands.…”
Section: Study Demographicsmentioning
confidence: 99%
“…Corroborando con los estudios anteriores, un estudio de cohorte (18) realizado con 141 pacientes durante un año, se centró en la evolución del servicio de derivación remota, controló el peso, los signos vitales y los signos y síntomas de descompensación cardíaca. Los datos obtenidos sobre peso se transmitieron a un registro médico central y electrónico.…”
Section: Estrategias Del Telecuidadounclassified
“…En el mismo estudio (18) citado anteriormente, la aplicación del puntaje del Instrumento de Calidad de Vida de Minnesota mostró una mejora progresiva en los parámetros trimestralmente; esto, a su vez, puede estar relacionado con un aumento en la confianza en su atención médica debido a la asistencia médica o en relación con una mejora en el vigor físico debido al control de peso. Otro parámetro relevante encontrado fue la disminución en la tasa de hospitalización por persona (4.7 a 2.6 p <0.001).…”
Section: Estrategias Del Telecuidadounclassified